ANALISIS PENGARUH SUDUT SAMBUNGAN DAN PEMILIHAN MATERIAL PADA DESAIN LADDER KAPAL PENGERUK SEDIMEN PERUM JASA TIRTA I: ANALYSIS OF THE EFFECT OF JOINT ANGLE AND MATERIAL SELECTION ON THE DESIGN OF THE SEDIMENT DREDGER SHIP LADDER AT PERUM JASA TIRTA I - Revaldy aditya pratama; Mujahid Wahyu; Ahmad Dzulfikri Halimi (Jurnal Teknik Mesin, 2025)
The modification of the dredger ladder at Perum Jasa Tirta I Workshop in Kediri has so far only involved an increase in length, without any changes to the shape or design model. The objective of this study is to analyze the influence of joint angle and material selection on the structural strength of the dredger ladder. The research method involves Finite Element Analysis (FEA) simulations using SolidWorks and ANSYS software to test variations in joint angles—30°, 45°, and 60°—and two types of steel materials: SS400 and ASTM A36. The simulation results show that the variation in angle affects the von Mises stress, with values of 278.16 MPa for SS400 and 271.21 MPa for ASTM A36. SS400 material has a higher safety factor, making it safer for ladder applications, although ASTM A36 also demonstrates better performance in terms of dynamic resistance. Overall, the combination of a 30° angle and SS400 material yields the best structural strength analysis results compared to other combinations.